2022
DOI: 10.3390/nu14091893
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Barrier Permeability in Allergic Diseases

Abstract: The role of intestinal permeability (IP) markers among children and adults with food allergies is not fully understood, and the identification of biological indicators/markers that predict growth retardation in children with allergic diseases and atopy has not been well explained. Studies have shown that patients with atopic diseases respond abnormally to food allergens. Accordingly, differences in the types of immune complexes formed in response to antigen challenges are significant, which seems to underlie t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 78 publications
0
34
0
1
Order By: Relevance
“…Food allergens can result in increased gut permeability and induce gut inflammation. Once the intestine is damaged, allergens will enter the peripheral circulation more smoothly, and will further intensify the allergic response [ 6 , 7 ]. In this study, we explored the efficacy of oral AVA on OVA-induced colonic injury in mice, and inquired about the possible mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food allergens can result in increased gut permeability and induce gut inflammation. Once the intestine is damaged, allergens will enter the peripheral circulation more smoothly, and will further intensify the allergic response [ 6 , 7 ]. In this study, we explored the efficacy of oral AVA on OVA-induced colonic injury in mice, and inquired about the possible mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of FA is characterized by the induction of T helper 2 (Th2) cell reaction induced by the disruption of oral tolerance to exogenous allergens [ 4 , 5 ]. It is worth noting that the overexposure to food allergens can result in the intestinal inflammation and mucosal barrier injury, which thus makes it easier for food allergens to enter the bloodstream, and then aggravates the allergic reaction and intestinal damage [ 6 , 7 ]. Therefore, it is necessary to explore effective strategies to relieve intestinal injury and inflammation induced by food antigens.…”
Section: Introductionmentioning
confidence: 99%
“…The apical junction complexes (AJCs) are one of the main components maintaining the integrity of epithelial barriers as they regulate cell-cell adhesion, cell polarity, and paracellular permeability of exogenous elements. These complexes are composed of two main structures, the tight junctions (TJs) and the adherens junctions (AJs) ( 36 38 ). TJs are formed by extracellular domains of transmembrane proteins (such as occludin and claudin protein families) that form strong links between them and connect with actin and tubulin cytoskeleton via scaffold proteins such as zonula occludens -1 (ZO-1) ( 39 ).…”
Section: Epithelial Barriers Play a Key Role In Allergy Developmentmentioning
confidence: 99%
“…An increased intestinal permeability was found in patients with AD ( 68 ), AA ( 69 ), and FA ( 70 ). It was suggested that the dysregulation of claudin-1, claudin-4, claudin-5, and claudin-8 impairs intestinal barrier integrity and leads to the increased allergen penetration ( 71 , 72 ). Moreover, the disruption of occludin raises intestinal permeability of macro-particles ( 73 ), which may contribute to the increased allergen entry.…”
Section: The Epithelial Barrier In Atopic Disordersmentioning
confidence: 99%